The Impact of Digital Gaming Experience on the Self-Concept of Students of Delhi NCR - Jain, Pallavi; Kumar, Harish; Rajput, Anup Kumar (Indian Journal of Educational Technology, 2024)
Children start to comprehend the universe at birth and eventually come to realize their own existence. They gradually establish their self-concept as they engage with their environment and start to identify who they are. Technological advancements have led to a rapid increase in the popularity of playing games on digital devices that offer a virtual space for users to interact through virtual avatars. Digital games have now largely taken the place of traditional toys in children’s lives. The gaming metaverse is gaining popularity as it is revolutionizing the cyberspace of gaming into an interactive and interesting 3D platform by providing immersive environments. This quantitative study aims to comprehend how students’ gaming experiences while engaging in virtual gaming platforms affect their self-concept, employing Robson’s Self-Concept Scale (1989) and the Gaming Experience Questionnaire (IJsselsteijn et al., 2013). The sample comprises students from Delhi NCR. The statistical tools used are mean, standard deviation, t-test, and Pearson’s correlation. The study elicits that female participants not only harbor a more positive self-concept but also demonstrate an enhanced involvement in gaming activities compared to their male counterparts. Similarly, age group distinctions manifest in self-concept and gaming experiences. The findings also illustrate that positive gaming encounters correlate with elevated self-concept, accentuating the intricate interplay between digital gaming experiences and self-concept formation.